Outage performance of multiple‐input–multiple‐output decode‐and‐forward relay networks with the Nth‐best relay selection scheme in the presence of co‐channel interference. Issue 15 (1st October 2014) - Li, Guoxin; Chen, Jin; Huang, Yuzhen; Ren, Guochun
Abstract : In this study, a dual‐hop multiple‐input–multiple‐output relay network with the N th‐best relay selection scheme in the presence of co‐channel interference is studied. Specifically, the N th‐best relay is selected based on the channel state information (CSI) of the first hop. The authors first consider the CSI is perfect feedback and derive exact as well as asymptotic closed‐form expressions for the outage probability. Results reveal that the diversity order of N R × min{ N S ( K − N + 1), N D } is achieved when there is no feedback delay, where N S, N R and N D represent the number of antennas at the source, the relays and the destination, respectively, K is the number of the relays and N (1 ≤ N ≤ K ) represents the rank of relay chosen. Then, they investigate the outage performance of the system with feedback delay, and exact and asymptotic outage probability expressions are also obtained. Results illustrate that outdated CSI degrades the diversity order of the system to min{ N R, N D }, which is independent of the number of antennas at the source, the number of relays and the rank of the relay chosen. The findings of the study provide valuable insights into the practical system design.